A Study of the Effectiveness of Lobby Strategies For Pharmacy As Percieved by Federal Legislators in Nigeria - G., Olayiwola; Babalola, O.O. (The Nigerian Journal of Pharmacy, 1996)
This work is the ﬁrst attempt in Nigeria at finding out which lobbying tactics is most suitable for pharmacy profession in getting favourable legislation from Government. A random sample of 300 legislators of the two houses of legislature - The Senate 14.3%, House of Representatives 85.6%, showed that constituency contact, expert witness and financial support are right mix of tactics to be employed by the Pharmacy Professional Organisation to elicit favourable legislation. Threat of harm, publication of voting records are the least favourable tactics. Ranking of the tactics by the two houses separately on ordinal scale showed that the legislation of both houses agree in their ranking ofthe lobbying tactics to be employed by the pham-racist (r/s=0.97). Lobbying apart from Direct Political Action is very important in impacting positive and effective legislation and regulation on Pharmaceutical Policies. A mix of these tactics is best depending on the situation.